Synonym-aid: improving vocabulary use in graph analysis using synonym cards - Mansor, Majdina; Abdul Hamid, Zaidatul Akmal; Saaidi, Nur Suhaila; Hussin, Muhammad Ekram (Asian Scholars Network, 2025)
English for Second Language (ESL) learners often face problems in writing due to limited vocabulary. Similar issues can be observed when students write essays for graph analysis. The literature suggests that vocabulary cards could improve writing. Undertaking action research in writing class, this study investigated the impact of using synonym cards on vocabulary use in graph analysis writing. This study sought to answer the following research questions: “How does Synonym-Aid improve vocabulary range in students’ graph analysis?” and “How does Synonym-Aid improve the students’ use of different noun and/or verb phrases?”. This qualitative study employed text analysis emphasizing on lexical components to measure word frequency, diversity, and use of specific vocabulary. The data set was essays of 35 students from two classes which were divided into two groups: control group and intervention group. Only the students in the intervention group were given Synonym-Aid during an in-class graph analysis writing task. The students’ essays from both groups were then graded using CEFR-aligned writing descriptors to assess vocabulary elements. The finding showed that students in the intervention group used a wider range of vocabulary including different verbs and noun phrases to describe similar trends. It can be concluded that, while students in the control group were able to use verb and noun phrases to describe trends, the vocabulary range was still somewhat limited. The study showed that direct and immediate intervention like synonym cards was able to improve vocabulary use in graph analysis writing.